Does the stock market punish corporate malfeasance?: A case study of Citigroup - Bruce Mizrach; Susan Zhang Weerts (Rutgers University, Department of Economics, 2005)
This paper examines how well the market anticipates regulatory sanction. We look at key dates of SEC, NASD, FTC, Congressional and foreign investigations and their subsequent resolution. Our event study confirms that the settlements provide little new information to the market. In six major case groupings, we find highly accurate predictions from market capitalization changes of settlements and associated private litigation.
Keywords: K22; 330; Event study; probe; SEC; settlement; subpoena